EFFECT OF FREQUENCY OF ORGANIC FERTILIZER FERTILIZER FROM MASSAGE TOWARDS GROWTH AND RED RESULTS - ran samiran samiran; Siti Hadijah Siti Hadijah; Agus Ruliyansyah Agus Ruliyansyah (Jurnal Sains Pertanian Equator, 2018)
This research was conducted in Experimental Garden of Faculty of Agriculture University of Tanjungpura Pontianak. The study was conducted for 3 months from November 2017 to January 2018. The purpose of this research is to know the effect of frequency of liquid organic fertilizer from snail mas to growth and red pepper plant yield. This research was done by Randomized Complete Random Design (RAL), with 4 treatment frequency of POC snail mas that is p0 = without permberian, p1 = 5 days, p2 = 10 days, p3 = 15 days. Each treatment was repeated six times, and each experimental unit consisted of 4 plant samples. The variables observed in this study were plant height, harvest age, number of fruit crops, plant fruit weight, fruit diameter, fruit length and dry weight of the plant. The results showed that the frequency of liquid organic fertilizer from snail mas had no significant effect on all observation variables.